Aryl Hydrocarbon Receptor is Essential in the Control of Lung Club Cell Homeostasis - Liu KY; Wang LT; Wang HC; Wang SN; Tseng LW; Chai CY; Chiou SS; Huang SK; Hsu SH (Dove Medical Press, 2021)
Kwei-Yan Liu,1 Li-Ting Wang,2 Hsueh-Chun Wang,3,4 Shen-Nien Wang,5– 7 Li-Wen Tseng,5 Chee-Yin Chai,8 Shyh-Shin Chiou,9,10 Shau-Ku Huang,1,11 Shih-Hsien Hsu5,12,13 1Department of Respirology & Allergy, Third Affiliated Hospital of Shenzhen University, Shenzhen, 518020, People’s Republic of China; 2Department of Life Science, National Taiwan Normal University, Taipei, Taiwan; 3Graduate Institute of Biomedical Sciences, China Medical University, Taichung, Taiwan; 4Department of Medical Research, China Medical University Hospital, China Medical University, Taichung, 40402, Taiwan; 5Graduate Institute of Medicine, College of Medicine, Kaohsiung Medical University, Kaohsiung, 807, Taiwan; 6Division of General and Digestive Surgery, Department of Surgery, Kaohsiung Medical University Hospital; 7Department of Surgery, College of Medicine, Kaohsiung Medical University Hospital, Kaohsiung, Taiwan; 8Department of Pathology, Faculty of Medicine, Kaohsiung Medical University, Kaohsiung, Taiwan; 9Division of Hematology-Oncology Department of Pediatrics, Kaohsiung Medical University Hospital Kaohsiung Medical University, Kaohsiung, Taiwan; 10Department of Pediatrics, Faculty of Medicine, College of Medicine, Kaohsiung Medical University, Kaohsiung, 807, Taiwan; 11National Institute of Environmental Health Sciences, National Health Research Institutes, Miaoli County, Taiwan; 12Department of Medical Research, Kaohsiung Medical University Hospital, Kaohsiung Medical University, Kaohsiung, 807, Taiwan; 13Research Center for Environmental Medicine, Kaohsiung Medical University, Kaohsiung, TaiwanCorrespondence: Shih-Hsien Hsu; Shau-Ku Huang Email jackhsu@kmu.edu.tw; skhuang@nhri.org.twBackground: Club cells play an important role in maintaining lung homeostasis and aryl hydrocarbon receptor (AhR) is known to be important in xenobiotic metabolism, but its role in regulating club cells is currently unknown.Methods: To this end, mice with club cell-specific AhR deficiency were generated and evaluated in a model of antigen (ovalbumin, OVA)-induced airway inflammation for the number of infiltrating inflammatory cells, the levels of cytokines and CC10 and Notch signaling by standard methods.Results: After OVA sensitization and challenge, Scgb1a1-Cre; Ahrflox/flox mice showed aggravated levels of pulmonary inflammation with increased levels of inflammatory cells and cytokines 1 day after challenge as compared to those seen in their littermate controls, but in contrast to the littermate controls, no significant change in the levels of CC10 and SP-D was noted in Scgb1a1-Cre; Ahrflox/flox mice. Surprisingly, 7 days after the challenge, while, as expected, wild-type mice recovered from acute inflammation, significantly increased lymphocytic infiltration was noted in Scgb1a1-Cre; Ahrflox/flox mice, suggesting their defective mechanism of recovery. Mechanistically, this was due, in part, to the decreased Notch1 signaling and expression of its downstream gene, HES5, while AhR was shown to positively regulate Notch1 expression via its transactivating activity targeting the xenobiotic response element in the promoter region of Notch1 gene.Conclusion: Under the condition of pulmonary inflammation, AhR is critical in controlling lung club cell homeostasis via targeting Notch1 signaling and the generation of anti-inflammatory mediators.Keywords: AhR, club cells, CC10, Notch1, Hes5